Kemitraan Multistakeholder dalam Pengelolaan Hutan Bersama Masyarakat di Kawasan Hutan Darajat Kabupaten Garut - Okke Rosmaladewi, Lilis Irmawatie (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2015)
The problem of forest resources in Darajat Forest Zone is a multidimensional problem, involving social issues, economics and the environment, yet the continuing process of forest degradation in particular. This is due to logging which is notbalanced the effort of established rehabilitation. Intercropping farming systems, plundering and illegal loggingin forests committed by the community made deforestation worse. Another important issues is the lackness of community role and the parties support outside Perum Perhutani KPH Garut, such as the district/village government, universities and non-governmental organizations so that rehabilitating the forest area is not considered as an optimal effort, still.Forest resources management model through multi-stakeholder partnerships which is done participatively, integratedly and sustainably starting from forest resources inventory,program planning, implementation and partnership monitoring programcan be implemented optimally. Multistakeholder Partnership Program in forest management suitable with the partnership principlesaretogetherness, equality, trust and mutual benefit. It is expected all stakeholders participate and contribute according to their role and function.